Respiratory outcomes after a 1-year treatment of obstructive sleep apnoea with bibloc versus monobloc oral appliances: a multicentre, randomized equivalence trial. (17th August 2020) - Tegelberg, Åke; Nohlert, Eva; Bornefalk-Hermansson, Anna; Fransson, Anette; Isacsson, Göran
Abstract: Objective: The benefit of bibloc over monobloc appliances in treating obstructive sleep apnoea (OSA) has not been evaluated in randomized trials. We hypothesized that these types of appliances would be equally effective. Material and methods: In this multicentre, randomized equivalence trial, patients with OSA received one type of bibloc or one type of monobloc treatment. At baseline, a 1-night polygraphy study was done, and this was repeated after 1 year. The outcome was any change in the apnoea–hypopnoea index (AHI) and the limits of equivalence between the two devices were set at ±5 AHI units. Results: Of 302 patients, 146 were randomly assigned to bibloc and 156 to monobloc appliances. In 88 and 104 patients, respectively, there were significant reductions in the AHI ( p  < .001) with a mean change of −16.7 (95% CI −19.4 to −14.1) in the bibloc and −11.8 (−14.9 to −8.7) in the monobloc groups. The proportions of responders defined as having an AHI <10 were 68% and 65% for the bibloc and monobloc groups, respectively. Treatment-related adverse events were mild, transient and the dropouts were more frequent in the bibloc group. Conclusions: Both types of treatments positively and significantly reduced respiratory disturbances, but at the 1-year follow-up, they were not significantly different in treating OSA, with a numerically greater reduction of the AHI value with the bibloc appliance. However, the higher proportion of treatment-related adverse events and higher proportion of dropouts among bibloc users should be balanced against the advantage of a greater reduction in the AHI.